Efforts to Improve The Learning Outcomes of Class IV Students in Natural Resources Materials Through Who's Quiz Card Media - Juriyah Juriyah (Universitas Sebelas Maret, 2020)
This research was motivated by the low activity and student learning outcomes through the initial study of natural resources material in grade IV SD Negeri Ciputih 02 with less than optimal student learning outcomes. This study aims to analyze the impact of using the Who I quiz card media on the learning outcomes of students. The research was conducted in two cycles, each cycle consisting of two meetings and four stages, namely: planning, acting, observing, and reflecting. In the first cycle there were 4 students (30.8%) and 9 students (69.2%) who had completed, with a class average score of 71.53. The results of cycle II reached 12 students (92.3%) and 1 student (7.7%) who had not completed, with a class average score of 80.76. Learning with the application of the right media produces good learning outcomes. It is proven that in each cycle there is a significant increase in learning outcomes. The conclusion is that the use of quiz card media who I am can improve student learning outcomes on natural resources material in class IV semester II SD Negeri Ciputih 02, Salem District, Brebes Regency.